If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3r + 11) = 7r + -3r Reorder the terms: 4(11 + 3r) = 7r + -3r (11 * 4 + 3r * 4) = 7r + -3r (44 + 12r) = 7r + -3r Combine like terms: 7r + -3r = 4r 44 + 12r = 4r Solving 44 + 12r = 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 44 + 12r + -4r = 4r + -4r Combine like terms: 12r + -4r = 8r 44 + 8r = 4r + -4r Combine like terms: 4r + -4r = 0 44 + 8r = 0 Add '-44' to each side of the equation. 44 + -44 + 8r = 0 + -44 Combine like terms: 44 + -44 = 0 0 + 8r = 0 + -44 8r = 0 + -44 Combine like terms: 0 + -44 = -44 8r = -44 Divide each side by '8'. r = -5.5 Simplifying r = -5.5
| 9x-58=26+6x | | 0.1x+40=180 | | h=50+69 | | -2x-7/3=7/13 | | 7x-58=30+11x | | 2x/6y*3y/4x | | G(x)=x^4-3x^2-4 | | 3x-75=-12x+135 | | -30z-0.8=-40z+1.7 | | 4x-11-6x+1=19-3x-1-3x | | -30z-0.8=40z+1.7 | | y=ln(5x^4-3x) | | y=-3f(x+5)+3 | | -8k-12= | | 12-0.4n= | | 96=w^2+4w | | 4x+54=180 | | 2/7x-1/6=8 | | 3x+21+3x-2=52-3x+39 | | 9x-15=11x+23 | | 8-2x=2x-8-8x | | 84=b^2-5b | | -7a=-11a-68 | | 4q^2-6q-4q^2+6q=4q^2-9 | | f(x)=2x^3+4x^2 | | 42=b^2-5b | | 8r+12ry-3xr-2xy= | | (-9x+2)-(-3x+-5)= | | x^2-3=-5 | | 9(2g+5)= | | 12x^5+15x^4+9X^2-4x=0 | | (1-z)(3z+5)=0 |